2020
DOI: 10.1017/jns.2019.40
|View full text |Cite
|
Sign up to set email alerts
|

Ficus deltoideaextract down-regulates protein tyrosine phosphatase 1B expression in a rat model of type 2 diabetes mellitus: a new insight into its antidiabetic mechanism

Abstract: Ficus deltoidea var. deltoidea Jack (FD) is a well-known plant used in Malay folklore medicine to lower blood glucose in diabetic patients. For further research of the antihyperglycemic mechanisms, the protein tyrosine phosphatase 1B (PTP1B)-inhibitory effect of FD was analysed both in vitro and in vivo. To optimise a method for FD extraction, water, 50, 70, 80, 90 and 95 % ethanol extracts were prepared and determined for their total phenolic and triterpene contents, and PTP1B-inhibition capacity. Among the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 89 publications
4
16
0
Order By: Relevance
“…The data support that the relationship between lipid pro le and sex hormones [48,49]. These results are also compatible with earlier studies demonstrating that F. deltoidea can reverse the abnormalities in the lipid pro le of diabetic rats [50] and adults with pre-diabetes [51].…”
Section: Discussionsupporting
confidence: 92%
“…The data support that the relationship between lipid pro le and sex hormones [48,49]. These results are also compatible with earlier studies demonstrating that F. deltoidea can reverse the abnormalities in the lipid pro le of diabetic rats [50] and adults with pre-diabetes [51].…”
Section: Discussionsupporting
confidence: 92%
“…Such histopathological modi cations were decreases by incorporation of AEEE extract at both doses. The current study agrees with previous studies on antidiabetic and anti-obesity effects of herbal extracts [53,54].…”
Section: Discussionsupporting
confidence: 93%
“…Choo et al [24] suggested the use of F. deltoidea as an antidiabetic since there exists both bioflavonoids (vitexin and isovitexin) in F. deltoidea plants. It was reported that the extract of F. deltoidea can potentially improve insulin sensitivity, suppress hepatic glucose output and enhance glucose uptake in type 2 diabetes mellitus through down-regulation of the protein tyrosine phosphatase 1B (PTP1B) [53]. They also stated the herb can be utilized as a useful remedy for alleviation of diabetes complications.…”
Section: Discussionmentioning
confidence: 99%